Structured instructional process and performance of Junior Secondary School 2 students in Mathematics - Olatoye, Mukaila Ayinde (Fakulti Pendidikan, Universiti Kebangsaan Malaysia, 2017)
This study examined the effectiveness and efficiency of using structured instructional process in teaching and learning substitution. The structured instructional process (object based card games) was compared with convention teaching methods in promoting achievement outcomes. A total of 120 Junior Secondary Schools II students (JSS2) drawn from three schools in three educational zones of Lagos state, Nigeria and three Mathematics teachers participated in this study. A mixed method of quantitative and qualitative was used with Analysis of Co-variance to analyse the data. Three research questions guided the study. The study was a pre and post test equivalent control group design. The results of the study showed that the treatments (Structured Instructional Object Based Games (SIOBG)) improved the subjects in grades and gained in knowledge over and above control group, that were exposed to the conventional methods. Gender and academic ability were not found to be significantly interacting with treatment.